Study on Properties of High Quality Silicon Mullite Brick - Cai1, Chuan-Chuan; Zhang2, Ming-Xu; Min2, Fan-Fei (Asian Journal of Chemistry, 2014)
Silicon mullite brick was prepared using high-grade bauxite and ultra-fine silicon carbide as main starting materials. In this study, the effect of zircon sand addition on the physical, chemical and mechanical properties of the bricks was investigated. The results showed that with the increase of zircon sand addition had a great effect on the physical and mechanical properties of the silicon mullite bricks. The bulk density and strength of the samples sintered at different temprature increased first and then declined,thermal shock resistance and alkali erosion of the samples increased significantly, when the optimum addition of zircon sand was 10-15 %, the silicon mullite brick had better alkali resistance.